The Effect of Financial Risk, Bonus Plan, and Managerial Ownership on Income Smoothing - Fima Fastaqima; Ayu Noviani Hanum; Alwiyah; Andwiani Sinarasri (www.amertainstitute.com, 2025)
This research seeks to investigate the impact of financial risk, bonus programs, and managerial ownership on income smoothing practices. The study's focus is on firms listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023 that are in the consumer industry subsector. The purposive sampling method was applied to intentionally select the samples. This study's data analysis was conducted using the EViews version 12 application and a panel data regression approach. The results of the research show that financial risk has a beneficial influence on income smoothing, whereas bonus programs have a negative effect. However, management ownership has insignificant effect on income smoothing.